The Influence of Project-Based Learning (PBL) and Motivation on Correspondence Learning Outcomes By Controlling Linguistic Intelligence - Mutmainnah, Sri; Sitanggang, Gartima; Simanullang, Rotua SP (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This research aims to ascertain (1) differences in correspondence learning outcomes for students taught with project-based learning (PBL) and those taught with the direct instruction (DI) model with controlling linguistic intelligence, (2) the influence of the interaction between the learning model and motivation study of students' correspondence learning outcomes by controlling linguistic intelligence, (3) differences in correspondence learning outcomes of students with high learning motivation taught with PBL and those taught with DI by controlling linguistic intelligence, and (4) differences in correspondence learning outcomes of students with low learning motivation who studied with PBL and those studied with DI by controlling linguistic intelligence. This research method employed a quasi-experiment with a 2 x 2 factorial design. The research sample for this study consisted of 68 students enrolled in the Department of Office Administration, specifically those taking Correspondence Subjects. The selection of participants was conducted through a random sampling method. The data analysis technique used two-way ANOVA at a significant level of α = 0.05. The study's findings demonstrated that (1) students instructed using PBL achieved higher correspondence learning outcomes than students taught using the DI model while controlling linguistic intelligence. (2) An interaction effect was observed between learning models and learning motivation on correspondence learning outcomes by controlling linguistic intelligence. (3) The learning outcomes of students with high learning motivation who studied with PBL were higher than students who studied with DI by controlling linguistic intelligence. Also, (4) the learning outcomes of students with low learning motivation taught with DI were higher than those taught with PBL by controlling linguistic intelligence. The results of this research denote that it is essential to adjust the learning model in Correspondence Subjects by considering students' learning motivation.